1991
DOI: 10.1159/000182106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pirenzepine, Bromocriptine and Their Association on Basal and GHRH- and TRH-Induced GH Secretion in Acromegaly

Abstract: In order to ascertain if pirenzepine (Pz), an antimuscarinic drug, could inhibit GH secretion in acromegaly, 8 patients were submitted to 3 successive treatment courses of 9 days each: Pz, bromocriptine (BRC) and Pz plus BRC. No change in basal levels of GH after Pz administration was seen, but its reduction (p < 0.05) by BRC was observed. Pz plus BRC did not improve this response. None of these drugs abolished the paradoxical GH response to TRH. In 7 normal controls, Pz suppressed the GH responsiveness to GHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
1

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
2
0
1
Order By: Relevance
“…As expected, on the basis of our previous reports (20,21) and others ( 11,18,19 ), we found that the antimuscarinic drug Pz was unable to block GH response to GHRH stimulus in untreated acromegalic patients. Although impaired cholinergic control of GH secre¬ tion is common in acromegaly, the pathophysiological mechanisms have not been sufficiently elucidated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As expected, on the basis of our previous reports (20,21) and others ( 11,18,19 ), we found that the antimuscarinic drug Pz was unable to block GH response to GHRH stimulus in untreated acromegalic patients. Although impaired cholinergic control of GH secre¬ tion is common in acromegaly, the pathophysiological mechanisms have not been sufficiently elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, cholinergic muscarinic receptor antago¬ nists, such as methoscopolamine, atropine and pirenzepine (Pz), virtually abolished the GH responses elicited by a series of physiological, hormonal and pharmacological stimuli, through an enhancement of hypothalamic SRIH secretion (7,16). These findings are in clear contrast to previous reports on acromegalic patients, in whom acute (11,(17)(18)(19) or chronic (20,21 ) administration of antimuscarinic drugs was unable to suppress basal, TRH-, GHRHand guanfacine-stimulated GH release. The neuroendocrine mech¬ anisms involved in this disturbance in acromegaly remain controversial.…”
contrasting
confidence: 99%
See 1 more Smart Citation